The Effect of Sucrose Proportion and Glutinous Rice Towards Organoleptic Properties on Dodol Banana Ambon - Masuku, Mustamin Anwar (Agrikan: Jurnal Agribisnis Perikanan, 2021)
The purpose of this study was to determine the organoleptic properties of banana fruit dodoo with the influence of the prorortion of sucrose and glutinous rice flour. With the treatment accordedthe G1T1 =Sucrose 400 g, 400 g glutinous rice flour,G2T1 =Sucrose 500 g,  400 g glutinous rice flour, and G2T2 = Sucrose 500 g, 500 g glutinous rice flour, and G3T2 = Sucrose 600 g, 400 g glutinous rice flour. Test carried out by organoleptic methods study was  conducted in a Completely Randomized Design (CRD) with 1 factors: faktor T = variation in starch and sucrose factor G =variation. At every level and every unit treatmen done 3 replicates so as to obtain 3x6=18 experimental units.then do the analysis that includes the organoleptic properties are: color,flavor and texture. All of the organoleptic properties (color,flavor and texture) gives a significantly different effect on the combination treatmen and observation. Organoleptic testing of the banana fruit dodoo with the treatment the proportion of sucrouse and glutinous rice flour produces different color values from 1.91 to 3.96 (very not-neutral brown), taste from 3.10 to 4.12 (neutral-taste banana) andtexture 2.05 to 4.40 (not chewy-chewy).of all the treatments dodoo banana fruit is best in this study was the proportion of sucrose and glutinous riceflour in trearmen (G1T1) with organoleptic results are: 3.77 color,flavor 4.12 and texture 4.15.